RETURN ON ASSETS (ROA) AND RETURN ON EQUITY (ROE) ON FIRM VALUE (INTERNATIONAL SEMINAR, 2024)
High company value is one of the determining factors for investors to invest. The purpose of this study was to determine the effect of Return on Asset (ROA) and Return on Equity (ROE) simultaneously and partially on the value of mining companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study uses secondary data in the form of financial reports and annual reports obtained from the Indonesia Stock Exchange website (http://www.idx.co.id/), as well as other sources. The sampling technique used purposive sampling method with multiple linear regression testing conducted on 56 mining sector companies. The results showed that ROA and ROE simultaneously had an influence on the firm value variable, while partially ROA and ROE did not significantly affect firm value.